1978
DOI: 10.1097/00000658-197803000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Acute Neurological Complications After Liver Transplantation with Particular Reference to Intraoperative Cerebral Air Embolus

Abstract: Nine of 48 adult patients who underwent orthotopic liver transplantation developed significant clinical neurological abnormalities recognized shortly after operation. Decrease in consciousness Otturred with resultant coma, focal and generalized seizures and the Ottasional appearance of a state or akinetic mutism. Neuropathologiall abnormalities consisted of mulUfocal areas of inrarction in cerebral cortex and basal ganglia in five patients, «Htral pontine myelinolysis in five (often more extensive than usuaUy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
3

Year Published

1982
1982
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 14 publications
(2 reference statements)
1
26
0
3
Order By: Relevance
“…2,13,14 The Birmingham study and others from abroad have suggested that neurologic complications occur in about 30% of patients and that these patients have a higher mortality and morbidity. 3,4,[6][7][8][9][10][11]13,[15][16][17] Although the overall survival of these patients posttransplant has improved dramatically over the years with the introduction of new surgical, medical, and, in particular, immunosuppressive techniques, there has been little change in the incidence of neurologic complications. In 1978, a study found neurologic complications in 19% of patients, 16 and 9 years later, in 1987, this figure was 33% of patients.…”
mentioning
confidence: 99%
“…2,13,14 The Birmingham study and others from abroad have suggested that neurologic complications occur in about 30% of patients and that these patients have a higher mortality and morbidity. 3,4,[6][7][8][9][10][11]13,[15][16][17] Although the overall survival of these patients posttransplant has improved dramatically over the years with the introduction of new surgical, medical, and, in particular, immunosuppressive techniques, there has been little change in the incidence of neurologic complications. In 1978, a study found neurologic complications in 19% of patients, 16 and 9 years later, in 1987, this figure was 33% of patients.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] These complications are a major cause of morbidity and mortality after LT. 7 In addition, post-LT neurological complications increase health care costs (mainly because of prolonged hospitalization) and worsen the health-related quality of life of these patients. 8 The most frequent clinical presentations are mental status changes (ranging from delirium to frank coma) with or without seizures.…”
mentioning
confidence: 99%
“…Their sizes are small and medium. 21 As our patient had infarction, her prognosis was considered to be relatively good and was potentially placed into the rehabilitation program.…”
Section: Discussionmentioning
confidence: 94%